Influence of nuclear factor κB and adenosine monophosphate-activated protein kinase on the vascular bed of the liver under the conditions of modeling chronic alcoholic hepatitis - MykytenkoA. О.; Akimov, O. Y.; Yeroshenko, G. A.; Neporada, K. N. (Regulatory Mechanisms in Biosystems, 2024)
Chronic alcohol use activates the transcription factor κB (NF-κB) in liver sinusoidal endothelial cells (LSECs), macrophages and other cells of the liver parenchyma, which controls the regulation of the expression of pro-inflammatory cytokines that activate signaling pathways of immune regulation of liver inflammation and vascular tone. AMP-activated protein kinase (AMPK) is an important immunometabolic regulatory factor in macrophages and, as a metabolic sensor, AMPK in vascular cells may be involved in the regulation of blood flow. The aim of the work was to find out the effect of modulators of the transcription factor κB and AMP-activated protein kinase on the morphometric parameters of the vascular bed of the liver of rats under the conditions of modeling chronic alcoholic hepatitis. Simulation of chronic alcoholic hepatitis leads to a violation of the exchange of metabolites between the central and interlobular veins, which creates prerequisites for the development of hypoxic damage to hepatocytes, as evidenced by a decrease in the diameters of lobular arterioles and venules. Administration of ammonium pyrrolidinedithiocarbamate and bacterial lipopolysaccharide, which affect NF-κB signaling under the conditions of modeling chronic alcoholic hepatitis, helps to restore the exchange of metabolites between the central and interlobular veins, which is evidenced by an increase in the lumens of lobular arterioles and venules. The introduction of phenformin and doxorubicin, which affect AMPK under the conditions of modeling chronic alcoholic hepatitis, prevents the development of hypoxic damage to hepatocytes, as evidenced by an increase in the diameters of lobular arteries and veins, and leads to intensification of interlobular blood circulation.